Perilaku UMKM Dalam Menggunakan Fintech: Fokus Regulatory dan Mitigasi Risiko - Muhammad Wildan Affan; Widyastuti, Aviani (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
The purpose of this research is to evaluate the use of fintech by conducting a study of the behavior of MSME actors, both that focus on promotion and focus on prevention of risk mitigation in the use of fintech. Data collected using a questionnaire with respondents who use MSME using fintech (payment). This study analyzes the data using the Structural Equation Model (SEM) by going through two stages of data analysis, namely evaluating the measurement model and testing the hypotheses that are built. The results showed that traits that focused on promotion would always try to choose risk while traits that focused on prevention would try to avoid risks. The risk mitigation of fintech carried out by users will increase according to the willingness of MSME actors to use fintech. So in other words, the higher the risk, the individual character that focuses on promotion and focuses on prevention will affect the intention to use fintech. Keywords: promotion focus, focus prevention, risk mitigation, fintech, MSME